Effect of particles with different mechanical properties on the energy dissipation properties of concrete. (30th July 2017) - Lu, Song; Xu, Jin-Yu; Bai, Er-Lei; Luo, Xin
Highlights: Flexible particles concrete and rigid particles concrete are prepared. Energy dissipation characteristics of different particles concrete are studied. Φ100 mm SHPB apparatus was improved by using the pulse shaper technique. As a new material, the development prospect has been discussed. Abstract: Expanded polystyrene concrete (flexible particles concrete) and alumina hollow ball concrete (rigid particles concrete) with volume content of 0%, 10%, 20%, 30%, 40% and 50% were prepared. In this paper, energy dissipation characteristics of different types of particles concrete were investigated, while the mechanism was analyzed. Impact compression experiments were carried out by a Ф100 mm split Hopkinson pressure bar (SHPB) apparatus which was improved by pulse shaping technique. Main conclusions are as follows: As for flexible particles concrete, the adding of flexible particles with volume content of 20% can effectively improve specific energy absorption and energy absorption of concrete, and the rigid particles concrete achieve the best energy absorption performance at the volume content of 40%. Through the analysis of fracture morphologies, the damage degree of the ordinary concrete and particles concrete increase as the incident energy change rate increases. The energy absorption performance of flexible particles concrete with volume content of 20% is better, compared with rigid particles concrete with volume content of 40%.Therefore, with volume content of 20%, the flexible particles concrete has characteristics of the most excellent energy dissipation and a wide development prospect in engineering application.